Monasteries and patrons in the Gorze reform Lotharingia c.850-1000 - Nightingale, John (John Bartholomew Wakelyn) (Oxford historical monographs., 2001)
The prominent role of monasteries in the early medieval period is examined in this illuminating study of the relations between monasteries and the nobility in Lotharingia throughout the 9th and 10th centuries.